Implementation of Village Fund Policy in the Distribution of BLT Funds in Gunung Singit Village, Silih Nara District, Central Aceh Regency - Muhammad Hasyem; Ferizaldi Ferizaldi; Dimas Prayogi; Devi Wulan Saliha (Master Program of Sociology, Universitas Malikussaleh,, 2023)
To overcome the problem of poverty related to the impact caused by the Covid-19 outbreak, one of the policies for handling the Covid-19 pandemic for the poor and new poor communities affected by Covid-19 is the Village Fund Direct Cash Assistance (BLT). The approach in this study uses a qualitative approach, which comprehensively describes the Implementation of the Village Fund Policy in the Distribution of BLT Funds and the factors that influence it in Gunung Singit Village, Silih Nara District, Central Aceh District. In order to obtain comprehensive and integrative data, as well as suitability between the data and the objectives of this study, the data were collected using techniques; interviews, observations and documents. The results showed that the implementation of BLT Fund Distribution in Gunung Singit Village, Silih Nara District, Central Aceh District was carried out in three stages, namely; a) The socialization stage, where at this stage the community is summoned/collected to be given direction, guidance, and procedures for using BLT funds; b) Data collection stage, this stage is the data/document collection stage where the Implementing Team/Team collects documents as a condition for receiving BLT Funds; c) The disbursement stage, where at this stage the people who have been registered and registered as BLT Fund recipients bring their identities in person and cannot be represented.